STUDENTSâ ABILITY FOR USING ELLIPTICAL CONSTRUCTION IN SENTENCES - Ramasari, Maria (JURNAL SMART, 2016)
Grammar is a fundamental thing in a language. The researcher assumes based on her observation that the hardest part of making and writing sentence is to arrange the words in a good sentence. Students are still confused when they are going to arrange the words in right grammar. In mastering grammar, students need time, opportunity, exercise and good teaching of grammar. Unfortunately, grammar skill is still lack attention in teaching and learning process. This research is intended to investigate and describe studentsâ ability for using elliptical construction in sentences. In this research, the researcher used descriptive method. The data was evaluated and analyzed to find out studentsâ ability for using elliptical construction in sentences by using percentage formula. There were 34 of 73 students who were in very low category with percentage 46.5%. The result of this research showed that studentsâ ability for using elliptical construction in sentences to the fourth semester students of English Study Program at Muhammadiyah University of Bengkulu was very low. It meant that the fourth semester English students still had lack knowledge and understanding about grammar: elliptical construction.Keywords: Studentsâ Ability, Elliptical Construction,and Sentences.